Comparison of the Effectiveness of Mindfulness-Based Cognitive Therapy and Well-Being Therapy on Health Indicators in Patients with Hypertension - Islami , Alireza; Mirzaian, Bahram; Khanmohammadi, Arsalan (KMAN Counseling & Psychology Nexus, 2025)
The aim of the present study was to compare the effectiveness of mindfulness-based cognitive therapy and well-being therapy on health indicators in patients with hypertension. This applied research, which utilized a field data collection method, employed a descriptive, interventional, and semi-experimental design with a pre-test, post-test, and control group format. The statistical population included all patients aged 45 to 55 years with hypertension who visited health centers and hospitals in the city of Babol during the first half of 2024 and had medical records. Based on inclusion and exclusion criteria and using a convenience sampling method, 45 participants were selected and divided into three groups: mindfulness-based cognitive therapy (15 participants), well-being therapy (15 participants), and a control group (15 participants). Data collection instruments included health indicators questionnaires, whose validity was confirmed by experts. Reliability was assessed using Cronbach's alpha coefficients, calculated as 0.79, 0.94, and 0.89, respectively. Data analysis was conducted using descriptive statistics (mean and standard deviation) and inferential statistics (Kolmogorov-Smirnov test and multivariate and univariate analysis of covariance) with SPSS 24 and Excel software. The results indicated significant differences in the effectiveness of mindfulness-based cognitive therapy and well-being therapy on the health indicators of patients with hypertension. Furthermore, mindfulness-based cognitive therapy was shown to be effective on the health indicators of these patients.